2021
DOI: 10.3389/fmicb.2021.699699
|View full text |Cite
|
Sign up to set email alerts
|

Phyllospheric Microbial Composition and Diversity of the Tobacco Leaves Infected by Didymella segeticola

Abstract: A Myriad of biotic and abiotic factors inevitably affects the growth and production of tobacco (Nicotiana tabacum L.), which is a model crop and sought-after worldwide for its foliage. Among the various impacts the level of disease severity poses on plants, the influence on the dynamics of phyllospheric microbial diversity is of utmost importance. In China, recurring reports of a phyto-pathogen, Didymella segeticola, a causal agent of tobacco leaf spot, accentuate the need for its in-depth investigation. Here,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 32 publications
4
23
0
Order By: Relevance
“…Besides, microbial genera were the highest at the third sampling stage. In high-throughput sequencing technology, the dominant fungal and bacterial phyla were Ascomycota and Proteobacteria, respectively, which is consistent with the results of a previous study (Huang et al, 2021). The top five fungal genera were Alternaria, Phoma, Symmetrospora, Cladosporium, and Psiloglonium, whereas the top five bacterial genera were Pseudomonas, Pantoea, Kosakonia, Ralstonia, and Sphingomonas; the dominant fungal and bacterial genus were Alternaria and Pseudomonas which were consistent with the result of previous studies (Xu et al, 2014;Liu et al, 2019Liu et al, , 2020.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Besides, microbial genera were the highest at the third sampling stage. In high-throughput sequencing technology, the dominant fungal and bacterial phyla were Ascomycota and Proteobacteria, respectively, which is consistent with the results of a previous study (Huang et al, 2021). The top five fungal genera were Alternaria, Phoma, Symmetrospora, Cladosporium, and Psiloglonium, whereas the top five bacterial genera were Pseudomonas, Pantoea, Kosakonia, Ralstonia, and Sphingomonas; the dominant fungal and bacterial genus were Alternaria and Pseudomonas which were consistent with the result of previous studies (Xu et al, 2014;Liu et al, 2019Liu et al, , 2020.…”
Section: Discussionsupporting
confidence: 91%
“…Moreover, the number of fungal OTUs was subject to change with an increase in disease severity. The α-diversity indices of fungi showed that there were no differences in the healthy group over time at the three leaf positions (Huang et al, 2021 ). A significant difference based on leaf types was observed where the relative abundance of predominant phyla, Ascomycota, and Basidiomycota from leaves infected by A .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The early bolting of Qianhu has largely been studied, but the role of plant microbiota, particularly rhizosphere microbiota, has not been considered. Didymella is a pathogen of tea leaf spots ( Huang et al., 2021 ). In the present study, this fungus was found to be the different fungus in the pre- and post-bolting stages of Qianhu.…”
Section: Discussionmentioning
confidence: 99%
“…Changes of phyllospheric fungi and bacteria can potentially be used to evaluate the effects of efficient disease management ( Huang et al, 2021a ). With the development of sequencing technology, the number of studies on phyllosphere microorganisms has gradually increased in recent years, creating a new era of phyllosphere microbial community research ( Hassani et al, 2018 ; Fitzpatrick et al, 2020 ; Gong and Xin, 2020 ).…”
Section: Introductionmentioning
confidence: 99%